Genome-wide association reveals novel genomic loci controlling rice grain yield and its component traits under water-deficit stress during the reproductive stage - Kadam, Niteen N; Struik, Paul C; Rebolledo, María Camila; Yin, Xinyou; Jagadish, Krishna S.V. (Oxford University Press, 2018)
A diversity panel comprising of 296 indica rice genotypes was phenotyped under non-stress and water-deficit stress conditions during the reproductive stage in 2013 and 2014 dry seasons at IRRI, Philippines. We investigated the genotypic variability for grain yield, yield components and related traits and conducted genome-wide association studies (GWAS) using high-density 45K single nucleotide polymorphisms. We detected 38 loci in 2013 and 64 loci in 2014 for non-stress conditions and 69 loci in 2013 and 55 loci in 2014 for water-deficit stress. Desynchronised flowering time confounded grain yield and its components in 2013 water-deficit. Statistically corrected grain yield and yield component values using days to flowering helped to detect 31 additional genetic loci for grain yield, its components and harvest index in 2013. There were few overlaps in the detected loci between years, between treatments, and when compared with previous studies using the same panel, indicating the complexity of yield formation under stress. Nevertheless, our analyses provided important insights into the potential links between grain yield with seed set and assimilate partitioning. Our findings demonstrate the complex genetic architecture of yield formation and proposes exploring genetic basis of less complex component traits as an alternative route for further yield enhancement.